The effectiveness of using interactive maps in teaching social studies to develop environmental awareness and visual thinking skills among tenth-grade students - Al-Ghafri, Mohammed Marzouq Dhafiyar (Journal of Curriculum and Teaching Methodology, 2025)
This study aimed to examine the effectiveness of using interactive maps in teaching social studies to enhance environmental awareness and visual thinking skills among tenth-grade female students. A quasi-experimental design was employed with a purposive sample of 72 students from Dhahira Governorate, divided into an experimental group (36 students taught with interactive maps) and a control group (36 students taught using traditional methods), with pre-equivalence verified for both groups. Two instruments were used: an environmental awareness scale consisting of environmental knowledge and environmental attitudes, and a visual thinking skills test. After administering the pre-tests, the unit “Environmental Issues and Hazards” was taught using an interactive map–based instructional guide, followed by post-testing. Results revealed statistically significant differences at (α = 0.05) in favor of the experimental group on both environmental awareness components and visual thinking skills, with a large effect size. Based on these findings, the study recommends developing interactive maps aligned with social studies content, adhering to their essential design components, and encouraging teachers to integrate them when teaching the “Environmental Issues and Hazards” unit.
Keywords: interactive maps; environmental awareness; visual thinking skills